Radiation Therapy Following Total Keloidectomy: A Retrospective Study over 11 Years - Kim, Kyuhee; Son, Daegu; Kim, Jinhee (Archives of Plastic Surgery, 2015)
Background Radiotherapy treatment after keloidectomy is known to be an effective method for reducing the rate of recurrence. However, to date, the appropriate total radiation dose and fractionation have not yet been confirmed. The authors performed a retrospective analysis to identify the appropriate radiation dose and fractionation in post-keloidectomy radiotherapy.Methods From May 2000 to February 2011, postoperative radiotherapy was performed on 39 lesions in 28 patients after total keloidectomy. The keloid lesions were confined to the ear lobes. Between May 2000 and May 2004, 14 keloids were treated with surgical excision, followed by a total radiation dose of 1,200 cGy in three fractions over four to five days (group 1). Between June 2004 to February 2011, 25 keloids were treated with surgical excision, followed by a total radiation dose of 1,500 cGy in three fractions over four to five days (group 2). Patients were given a survey asking them to report their experiences regarding reoperation, recurrence of symptoms, recurrence of the lesion, and satisfaction with the operation.Results Of the 28 patients who were treated, 20 underwent follow-up. Group 2 had more cases showing elevation with erythematous changes, whereas group 1 had more cases showing progressive stages of elevation than group 2. These differences were statistically significant. Moreover, a correlation was observed between the level of keloid elevation and the extent of symptoms.Conclusions We suggest 1,500 cGy of radiation in three fractions following keloidectomy for ear lobe keloids. A further randomized study is needed to assess the recurrence of keloids after radiotherapy.
Keywords: Keloid; Radiation; Ear